1995
DOI: 10.1111/j.1745-4557.1995.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Levels of Fresh and Processed Spinach Using Ion Chromatography

Abstract: The anion (Cl-, NO,, So:-, PO:., OX2-) and cation (Nai, Ki, NH4') composition of raw, frozen and canned spinach samples was determined by Ion Chromatography (IC). In general, the levels of these ions were determined after typical food processing operations. Important for its health-related and nutritional point of view is the observation that nitrate levels decreased by about 50% with losses of 15% in total organic nitrogen after typical commercial processing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The data in Table 1 shows the ion concentration in the water samples and demonstrates the losses detected in chloride, nitrate, phosphate, sulphate and oxalate in raw spinach samples during processing for freezing or canning. In fact, when spinach samples in different stages of processing are analysed, we observed that the chloride levels fell (Vera et al . 1995).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The data in Table 1 shows the ion concentration in the water samples and demonstrates the losses detected in chloride, nitrate, phosphate, sulphate and oxalate in raw spinach samples during processing for freezing or canning. In fact, when spinach samples in different stages of processing are analysed, we observed that the chloride levels fell (Vera et al . 1995).…”
Section: Resultsmentioning
confidence: 90%
“…1995). The decrease in nitrate levels in spinach samples (Vera et al . 1995) reflects the increase observed in the various waters as described above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations